Experimental and theoretical investigation of cyclohexanone derivative (CHD) as a corrosion inhibitor for mild steel in 1 M HCl - B. M. Praveen; A. S. Jeevan Chakravarthy; B. M. Prasanna; Shabanbanu; Bharath K. Devendra; M. K. Pavithra; Fasiulla (Scientific Reports)
Abstract Newly synthesized 1-bromo-2-(4-bromophenylsulfonate)-4,4-dimethyl-1-cyclohexenyl-6-one (CHD) as a potential anticorrosive agent in an acidic medium at an elevated temperature range of 305–335 K. This synthesized compound confirmed by spectral characterizations and it acts as a coating on mild steel surfaces in 1 M Hydrochloric acid (HCl) solution through electrochemical reactions. The synthesis of the compound has been discussed, and the Infrared (IR) and Nucleic Magnetic Resonance (NMR) spectral analysis confirmed the derivative. Afterward, the synthesized compound was subjected to various electrochemical investigations. This suggested that in 1 M Hydrochloric acid (HCl), the compound efficiently prevents mild steel corrosion. Potentiodynamic polarisation studies demonstrate that the Ecorr values for treated and untreated samples are within ± 85 mV, compound inhibits mild steel in 1 M Hydrochloric acid (HCl) via a mixed-type mechanism. Electrochemical techniques have proved the potential of the synthesized compound as a corrosion inhibitor bearing a maximum inhibition efficiency greater than 95% for optimised concentrations up to 25 ppm. The obtained results are supported by scanning electron microscopic images, thermodynamic parameters, and quantum mechanical considerations. ΔG 0 ads value from thermodynamic studies indicates the spontaneous adsorption of the inhibitor compound onto the Surface of mild steel.